2012
DOI: 10.1155/2012/435463
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Kinetics of Serum MMP-9 and TIMP-1 after Blunt Multiple Injuries in the Early Posttraumatic Period

Abstract: Metalloproteinases are secreted in response to a variety of inflammatory mediators and inhibited by tissue inhibitors of matrixmetalloproteinases (TIMPs). Two members of these families, MMP-9 and TIMP-1, were differentially expressed depending on clinical parameters in a previous genomewide mRNA analysis. The aim of this paper was now to evaluate the posttraumatic serum levels and the time course of both proteins depending on distinct clinical parameters. 60 multiple traumatized patients (ISS > 16) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Brumann et al [26] found the highest MMP-9 levels immediately after admission in polytrauma casualties, whereas TIMP-1 were increased significantly during the whole 72-hour study period after a low admission level. These enzyme concentration kinetics are in concordance with our results.…”
Section: Discussionmentioning
confidence: 96%
“…Brumann et al [26] found the highest MMP-9 levels immediately after admission in polytrauma casualties, whereas TIMP-1 were increased significantly during the whole 72-hour study period after a low admission level. These enzyme concentration kinetics are in concordance with our results.…”
Section: Discussionmentioning
confidence: 96%
“…MMP-9 (a 92 kDa gelatinase) is a type IV collagenase implicated in various aspects of inflammation including accumulation of inflammatory cells, healing of tissue injury, and remodeling processes (Brumann et al 2012). It is produced by epithelial and endothelial cells, fibroblasts, platelets, neutrophils, eosinophils, and macrophages (Iyer et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to its normotensive control, the Wistar Kyoto Rat (WKY), MMP levels, specifically MMP-2 and MMP-9, in the SHR are elevated (Chen et al, 2012; DeLano & Schmid-Schönbein, 2008; Tran et al, 2010), leading to ectodomain receptor cleavage and cellular dysfunctions (Chen et al, 2010; Delano et al, 2011; DeLano & Schmid-Schönbein, 2008; Rodrigues et al, 2010; Tran et al, 2010) generating its co-morbidities, such as insulin resistance. Levels of the endogenous tissue inhibitors of metalloproteinases (TIMPs), such as TIMP-1 and TIMP-2 with the ability to inhibit MMP-9 and MMP-2, respectively (Bernardo & Fridman, 2003; Brumann et al, 2012) are undetermined and will be presented in this report.…”
Section: Introductionmentioning
confidence: 99%